Making adaptive rigour work - Principles and practices for strenghenin g monitoring, evaluation and learning for adaptive management - Ramalingam, Ben; Wild, Leni; Buffardi, Anne L (ODI/GLAM, 2019)
Adaptive programmes can be accountable, rigorous and high quality in h ow they use evidence by taking an ’adaptive rigour’ approach. Core dev elopment and humanitarian challenges are complex, and require processe s of testing, learning and iteration to find solutions – adaptive mana gement offers one approach for this. Yet large bureaucracies and devel opment organisations can have low tolerance for experimentation and le arning, and adaptive management can be viewed as an excuse for ‘making things up as you go along’. This briefing from the Global Learning fo r Adaptive Management (GLAM) initiative argues that adaptive programme s can be accountable, rigorous and high quality in how they use eviden ce – but this requires rethinking some key assumptions about how they are practised. The paper sets out three key elements of an ‘adaptive r igour’ approach: - Strengthening the quality of monitoring, evaluation and learning data and systems. - Ensuring appropriate investment in m onitoring, evaluation and learning across the programme cycle. - Stren gthening capacities and incentives to ensure the effective use of evid ence and learning as part of decision-making, leading ultimately to im proved effectiveness.